A screening tool for clinically relevant urinary incontinence. Issue 4 (25th January 2014) - Suskind, Anne M.; Dunn, Rodney L.; Morgan, Daniel M.; DeLancey, John O. L.; Rew, Karl T.; Wei, John T.
<x xml:space="preserve">Abstract</x> Aims The Michigan Incontinence Symptom Index (M‐ISI) is a validated measure for urinary incontinence. This study evaluates the M‐ISI as a screening tool for clinically relevant urinary incontinence in a population‐based sample of women. Methods The Establishing the Prevalence of Incontinence (EPI) Study is a case‐control, population‐based study that enrolled women ages 35–64, with and without urinary incontinence. The M‐ISI is a validated questionnaire with subdomains for stress and urgency urinary incontinence. Two hundred fourteen EPI subjects underwent a clinical evaluation and urodynamic testing to establish the presence and type of urinary incontinence, and also completed the M‐ISI. The M‐ISI scores were evaluated using receiver operating characteristic (ROC) curves to determine the optimal diagnostic threshold scores above which women were likely to have clinically relevant urinary incontinence. Results The optimal M‐ISI diagnostic threshold scores were determined to be ≥3 for the stress urinary incontinence subdomain (area under the curve of 0.79), ≥5 for the urgency urinary incontinence subdomain (area under the curve of 0.88), and ≥7 for the Total M‐ISI score (area under the curve of 0.89). The sensitivity and specificity of the M‐ISI questionnaire for stress, urgency, and total urinary incontinence were 77% and 73%, 86% and 76%, and 84% and 75%, respectively. Conclusions The M‐ISI may be used to screen for clinically relevant urinary incontinence with high sensitivity and specificity among women ages 35–64. A brief, self‐administered tool such as the M‐ISI can help health care providers identify and manage women with urinary incontinence. Neurourol. Urodynam. 34:332–335, 2015. © 2014 Wiley Periodicals, Inc.